2013
DOI: 10.1371/journal.pone.0061361
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Safety of Interferon for Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe effect of interferon(IFN) in the management of hepatocellular carcinoma (HCC) remains controversial, and no clear recommendations have been proposed.ObjectivesTo evaluate the effect and safety of IFN for HCC.MethodsPubMed, OvidSP, and Cochrane Library were searched from their establishment date until August 30, 2012. Studies that met the inclusion criteria were systematically evaluated and then subjected to meta-analysis.ResultsThirteen randomized control trials (RCTs) involving 1344 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Nineteen meta-analyses compared the outcomes of antiviral therapy versus no antiviral therapy (Supplementary Table S2) [10, 49, 54, 56, 58, 8486, 103, 105, 107, 112, 120, 128, 139, 142, 154, 158159]. Thirteen of them favored the use of antiviral therapy in term of OS [10, 49, 54, 84, 86, 105, 107, 112, 120, 128, 139, 142, 154]; one found that the use of antiviral therapy significantly improved the 5-year survival in HCV patients, but not HBV patients [58]; one demonstrated that the 1-year survival was statistically similar between the two groups [56]; one showed that 1-, 2-, 3-, 4-, and 5-year survival were statistically similar between the two groups [159]; another three did not report the survival data [85, 103, 158].…”
Section: Tacementioning
confidence: 99%
“…Nineteen meta-analyses compared the outcomes of antiviral therapy versus no antiviral therapy (Supplementary Table S2) [10, 49, 54, 56, 58, 8486, 103, 105, 107, 112, 120, 128, 139, 142, 154, 158159]. Thirteen of them favored the use of antiviral therapy in term of OS [10, 49, 54, 84, 86, 105, 107, 112, 120, 128, 139, 142, 154]; one found that the use of antiviral therapy significantly improved the 5-year survival in HCV patients, but not HBV patients [58]; one demonstrated that the 1-year survival was statistically similar between the two groups [56]; one showed that 1-, 2-, 3-, 4-, and 5-year survival were statistically similar between the two groups [159]; another three did not report the survival data [85, 103, 158].…”
Section: Tacementioning
confidence: 99%
“…Clinical testing suggestive of positive activity has involved the use of adaptive transfer of lymphocytes, autologous tumor-pulsed dendritic cells (DCs) and alpha-fetoprotein (AFP) -pulsed DCs, but no significant tumor regression or survival response has been observed [17]. The use of interferon remains controversial insofar as clinical trials demonstrated reduced recurrence rates but without overall survival effect even when used in the adjuvant setting [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it might be possible that tumors will develop in the future even after HCV elimination when only a DAA regimen is used. Much like the reports demonstrating that IFN treatment has the ability to suppress the growth of hepatocellular carcinoma,45, 46 our new finding that RBV has the ability to suppress lipogenesis in hepatic cells will shed light once again on the beneficial abilities of RBV not only for antiviral but also antipathogenic treatments of liver diseases, such as hepatic steatosis or hepatocellular carcinoma, in which aberrant lipogenesis is involved.…”
Section: Discussionmentioning
confidence: 70%